PROMOTING SCIENTIFIC AND TECHNOLOGICAL LITERACY AMONG POSTGRADUATE STUDENTS AT THE FACULTY OF EDUCATION UTM - Seth Sulaiman; Md Nor Bakar; Mohammad Yusof Arshad; Zaleha Ismail; Fatin Aliah Phang Abdullah (Program Pascasarjana Universitas Negeri Jakarta, 2014)
One important issue in the Science Education debate over the last century was how to preparea more relevant science education of the 21st Century that emphasizes on promoting scientificliteracy through a more meaningful science education program. In response to this call, ageneral science education elective course code named MPS1163 Epistemological, Social andEthical Issues in Science and Technology was designed and implemented starting in Semester2 Session 2009/2010. By the end of Semester 2 Session 2012/2013 the course has been runningfor 7 semesters and had invited 128 postgraduate students from 7 different programs, includinga PhD program. A questionnaire was distributed to 26 course participants at the end ofsemester 2 Session 2012/2013. The objective of the questionnaire was to seek their personalassessment on their knowledge and understanding on the eleven course contents taken duringthe whole semester. The results indicated that there was a mean increment of between 40- 50%on their knowledge and understanding on the topics covered compared to their knowledge andunderstanding before taking the course. The second part of the questionnaire consisted of sixitems, using five point Likert Scale, seeking their suggestions for improving a more relevantscience education through the elective course. The response was commendable. Implicationsof the study related to course contents and students opinions on the course contents andsuggestions for the improvement of the course are discussed in this paper.Keywords: scientific literacy, technological literacy, general education elective course, a morerelevant science education.